EVALUASI IMPLEMENTASI KURIKULUM MERDEKA DI SDIT SWASTA DAFA BINJAI - Wiwik Safura; Sri Wahyuni Daulay; Nurul Huda Zulfiani; Ahmad Fauzan Shidiq Nasution (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
His study aims to evaluate the implementation of the Merdeka Curriculum at SDIT Swasta Dafa Binjai using the CIPP (Context, Input, Process, Product) evaluation model. This research was motivated by the importance of curriculum evaluation in improving educational quality and ensuring that the implementation of the Merdeka Curriculum aligns with its intended objectives. The study employed a qualitative approach with a descriptive-evaluative design. Data were collected through in-depth interviews and documentation. The research informant was the Vice Principal for Curriculum Affairs at SDIT Swasta Dafa Binjai. Data analysis used the Miles, Huberman, and Saldaña interactive model consisting of data reduction, data display, and conclusion drawing. The findings indicate that, in terms of context, the implementation of the Merdeka Curriculum aligns with government policies, the school's vision and mission, and the characteristics of an integrated Islamic school. In terms of input, the school has adequate facilities and supporting programs, although teachers' competencies still need improvement. In terms of process, learning activities have implemented student-centered learning, differentiated instruction, and the Pancasila Student Profile Strengthening Project (P5). In terms of product, the implementation of the curriculum has positively impacted the quality of learning and students' religious character development. The study recommends strengthening teacher competencies, enhancing collaboration with parents, and developing more objective instruments for assessing students' character development